Methodological strategies used in engineering: a systematic review - Tepe Atoche, Victor Manuel (2020)
The training of engineers is a subject that involves teachers and students, technological advances force higher education centers to seek alternatives to improve or propose new teaching strategies in engineering. The objective of the Research carried out was to make a bibliographic review in a qualitative way, which allows us to know the teaching methodologies strategies used by teachers in engineering careers at universities in Latin America and the world, taking into consideration the impact that these generate in the training of future engineers, it was considered forty (40) articles published between the years 2010 to 2020 that are related to training processes, the Google Scholar search engine and the search equations were used, in order to find in databases the information, which will allow us to make an analysis of the development of methodological strategies that teachers use in the training of future engineers, this does not lead to the conclusion that it is still an area that needs to be addressed by researchers.